Signature whistle use and changes in whistle emission rate in a rehabilitated rough-toothed dolphin - Ramos, Eric A.; Jones, Brittany L.; Austin, Maia; Eierman, Laura; Collom, Kristi A.; Melo-Santos, Gabriel; Castelblanco-Martínez, Nataly; Arreola, Marıá Renée; Sánchez-Okrucky, Roberto; Rieucau, Guillaume (Frontiers in Marine Science, 2023)
Acoustic signals play a crucial role in communication among animals, particularly in dolphins. Signature whistles, one of their most extensively studied vocalizations, enable dolphins to convey their identity to conspecifics through individually distinct whistle contours. However, it remains unclear whether rough-toothed dolphins (Steno bredanensis) also produce signature whistles with individually identifying contours and, if so, whether they are associated with stress and poor health, such as in bottlenose dolphins. To bridge this knowledge gap, we recorded sounds emitted by a live-stranded rough-toothed dolphin during its rehabilitation in May 2017 at Isla Mujeres, Quintana Roo, Mexico. We assessed if the dolphin produced a signature whistle and whether whistle rate, inter-whistle interval, mean low and high frequencies, and blood chemistry measures, changed significantly over time. Our findings revealed that while isolated from conspecifics during rehabilitation, the dolphin generated a single, repeated, and stereotyped whistle contour that met the previously established SIGnature IDentification criteria for signature whistle emissions for bottlenose dolphins. Whistle characteristics varied over the 11 recording days: whistle rate and inter-whistle interval significantly decreased over time; the number of whistles with preceding echolocation click trains decreased over time; and mean low and high frequencies changed over recording days. We conclude that this rough-toothed dolphin possessed what resembles a signature whistle contour, and the emission of this contour underwent significant changes throughout the rehabilitation process. While our study presents evidence of a single rough-toothed dolphin producing a signature whistle, further research is necessary to determine whether this vocal behavior is prevalent across the species.